Case Report of a Glioma Patient with Homozygous Missense Amino Acid Substitution in KDR Gene - Uppaluri, Kalyan Ram; Kambalachenu, Himavanth Reddy; Challa, Hima Jyothi; Y., Saadvik Raghuram; Sharma, Deepak; Gadicherla, Ramya; Ketavath, Srinivas; Palasamudram, Kalyani; K., Sri Manjari (Indian Journal of Medical and Paediatric Oncology, 2023)
Gliomas are the most commonly seen cancers of the central nervous system with a variable genetic predisposition. Here, we report a homozygous missense variant in the KDR gene in a patient with recurrent glioma. The 35-year-old male patient was diagnosed with stage IV glioma with a recurrence after 10 years from a low-grade stage two glioma. The patient underwent a repeat right craniotomy and ventriculoperitoneal shunt placement. Biopsy of the lesion showed areas of necrosis with microvascular proliferation and multinucleated tumor cells. An in-depth analysis of NGS data comprising a multigene panel of 351 genes (Agilent Cancer Core Panel) found a homozygous missense variant in exon 25 of the KDR gene that resulted in a substitution of an amino acid glutamine for arginine at codon 1118. The KDR gene or VEGF2 receptor is a type III receptor tyrosine kinase of the VEGF gene involved in angiogenesis. We hypothesize that the variation in the KDR gene may have a role in the patient's transition from grade II to grade IV glioma. While the clinical relevance of this mutation is not clear, screening mutations in the protein tyrosine and serine/threonine kinase domain of the KDR will provide critical insights into the development and progression of glioma in the pediatric and adult populations.
Keywords: glioma; Protein Kinase; KDR